2013
DOI: 10.4074/s0003503313014012
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of future reading skills: A follow-up of French-speaking children from the beginning of kindergarten to the end of the second grade (age 5 to 8)

Abstract: International audienceWe reported the results of two studies on the early predictors of future reading skills. The main goal of the first study was to examine whether reading level at age 8 can be predicted on the basis of a skill very rarely examined in longitudinal studies: phonemic discrimination. Two groups of French-speaking children were selected based on their phonemic discrimination skills at age 5: a group with low skills and a group with average to high skills in that domain. These two groups were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 39 publications
0
8
0
10
Order By: Relevance
“…We did this for several reasons. First, these dimensions predict future skills (Duncan et al, 2007; Kendeou, van den Broek, White, & Lynch, 2009; Piquard‐Kipffer & Sprenger‐Charolles, 2013; Catts, Herrera, Nielsen, & Bridges, 2015). Second, they are some of the most widely studied aspects of EL (Lonigan, Schatschneider, & Westberg, 2008).…”
Section: The Dimensions Of Early Literacymentioning
confidence: 99%
“…We did this for several reasons. First, these dimensions predict future skills (Duncan et al, 2007; Kendeou, van den Broek, White, & Lynch, 2009; Piquard‐Kipffer & Sprenger‐Charolles, 2013; Catts, Herrera, Nielsen, & Bridges, 2015). Second, they are some of the most widely studied aspects of EL (Lonigan, Schatschneider, & Westberg, 2008).…”
Section: The Dimensions Of Early Literacymentioning
confidence: 99%
“…In French, very few studies have been conducted in children from before the beginning of formal reading instruction. As one exception, Piquard-Kipffer and Sprenger-Charolles (2013) performed a follow-up study of French-speaking children from the beginning of kindergarten to the end of second grade and showed that a high proportion of the variance in reading at Age 8 (52.8%) was predicted by the “classical” predictors of reading acquisition assessed at Age 5: pre-reading level, letter-name knowledge, phonemic segmentation and phonological short-term memory.…”
Section: From Early Literacy To Success In Reading: What Are the Predmentioning
confidence: 99%
“…Aksara Bahasa Indonesia memiliki cerita yang panjang. Semua aksara yang ada di Indonesia pada masa lalu berbeda dengan aksara yang digunakan saat ini (Roza, 2017 -Kipffer & Sprenger-Charolles, 2013;Stanovich, 2005). Kesadaran fonologi adalah kemampuan seseorang terhadap bunyi-bunyi yang membentuk kata yang diucapkan.…”
unclassified